Physical Activity and Body Composition Are Associated With Severity and Risk of Depression, and Serum Lipids - von Zimmermann, Claudia; Winkelmann, Merle; Richter-Schmidinger, Tanja; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Frontiers in Psychiatry, 2020)
Backround: Physical activity and healthy body composition are said to reduce the risk of major depressive disorder. Nonetheless, deeper insight is needed into exactly which forms of physical activity (and their relation to body composition) are effective in preventing and improving depressive symptoms. Methods: We compared different physical activities of the Global Physical Activity Questionnaire and body composition measures between patients with a current major depressive episode (MDE; n=130) and healthy control subjects (n=61). These parameters were also tested for correlations with depression severity and serum lipid levels in patients and controls. Results: Patients with a current MDE reported fewer hours spent on total physical activity, walking or bicycling for travel, and vigorous-intensity activities at leisure than healthy control subjects. More time spent on vigorous-intensity activities at work, less on walking or bicycling for travel, higher body fat mass, and lower body muscle mass correlated with stronger depression severity. Physical activity and body measures correlated with serum lipid levels. Limitations: Self-reports of physical activity, only short-term follow-up of 20 days. Conclusions: More time spent on traveling by foot or by bike and vigorous-intensive physical activity at leisure are especially associated with a lower risk of and milder depression. These results highlight the differential role of physical activity in depression.